Effect of Macroeconomic Indicators and CO2 Emission on Indonesian Economic Growth - Prawoto, Nano; Basuki, Agus Tri (International Journal of Energy Economics and Policy, 2020)
The purpose of this study is to identify the impact of the value of trade, investment, the exchange rate of the rupiah against the dollar, industrial added value, and oil consumption and carbon dioxide emissions on Indonesia’s economic growth. This study uses data from 1986 to 2018 and uses the ECM model. The results of this study are the value of trade, investment, exchange rates and industrial added value have an influence on economic growth both in the short and long term. Oil consumption and CO2 emissions only have an influence in the long run. CO2 emissions are the engine of economic growth, so Indonesia must change its economic development strategy that is environmentally friendly so that the next generation can utilize natural resources without damaging the environment. The use of natural resources in development needs to pay attention to environmental conditions so that environmental ecosystems are not disturbed. Keywords: Economic Growth, Error Correction Model, CO2 Emissions, Environmental Economics. JEL Classifications: E27, E44, Q5 DOI: https://doi.org/10.32479/ijeep.10031